The role of quantitative sensory testing in the prediction of chronic pain - Treede, Rolf-Detlef (Pain, 2019)
AbstractQuantitative sensory testing (QST) is a formal variant of a time-honoured clinical examination technique in neurology, the sensory examination. Prototypical QST profiles have been found in human surrogate models of peripheral sensitization, central sensitization, and deafferentation. Probabi
Gesehen am 24.02.2020